Perancangan E-Learning Berbasis Blended Learning dalam Pembelajaran Fluida Statis - Nurahmih, Silva; Muliyati, Dewi; Permana, Handjoko (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Abstract The application of e-learning in education has become increasingly essential for enhancing learning effectiveness, particularly in physics topics such as static fluids. This study aims to design a blended learning–based e-learning system to improve students’ understanding of static fluid concepts. The research employs a research and development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation), integrated with Moodle’s built-in feature, Activity Analytics, to monitor students’ learning progress and engagement. The results indicate that the blended learning design integrated into Moodle consists of key components, including interactive learning materials, collaborative activities through discussion forums, quizzes for evaluation, and the use of Activity Analytics to track students’ learning progress. This design is expected to support the development of more adaptive learning features that accommodate students’ individual learning needs. Abstrak Penerapan e-learning dalam dunia pendidikan menjadi semakin penting untuk meningkatkan efektivitas pembelajaran, khususnya pada materi fluida statis. Penelitian ini bertujuan untuk merancang e-learning berbasis blended learning yang dapat meningkatkan pemahaman siswa terhadap konsep fluida statis. Metode penelitian yang digunakan adalah pendekatan research and development (R&D) dengan model ADDIE (Analyze, Design, Development, Implementation, dan Evaluation), serta memanfaatkan salah satu fitur bawaan Moodle, yaitu Activity Analytics, untuk memantau aktivitas dan perkembangan belajar siswa. Hasil pengembangan menunjukkan bahwa desain blended learning yang terintegrasi dengan Moodle mencakup komponen utama berupa materi pembelajaran interaktif, aktivitas kolaboratif melalui forum diskusi, kuis sebagai sarana evaluasi, serta pemanfaatan fitur Activity Analytics untuk memantau progres belajar siswa. Melalui desain ini, diharapkan dapat dikembangkan fitur pembelajaran yang lebih adaptif guna memenuhi kebutuhan belajar individu siswa.